Investigation of the Electrochemical Mechanisms for Acetic Acid Corrosion of Mild Steel - Tran, Thu; Brown, Bruce; Nesic, Srdjan; Tribollet, Bernard (CORROSION, 2014)
International audience Acetic acid (CH3COOH) is recognized as an important factor in mild steel corrosion. Similar to carbonic acid (H2CO3) present in carbon dioxide (CO2)-saturated aqueous environments, acetic acid is a weak acid, which partially dissociates with the equilibrium being a function of pH and the solution temperature. Stronger than carbonic acid (pKa 4.76 vs. 6.35 at 25°C), acetic acid is the main source of hydrogen ions when the concentration of each acid is the same. Based on many different studies, it is agreed that acetic acid enhances the corrosion rate of mild steel by accelerating the rate of the cathodic (reduction) reaction. However, the electrochemical mechanism of acetic acid reduction at the metal surface is still being debated. One possibility is for the undissociated acetic acid to provide additional hydrogen ions by dissociation near the metal surface. In that case the main cathodic reduction is hydrogen ion reduction, and this mechanism is commonly referred to as a "buffering effect." If, in addition to this pathway for hydrogen evolution, there is a reduction of the adsorbed undissociated acetic acid at the metal surface, the mechanism is known as "direct reduction." In the present study, electrochemical techniques were used to investigate the effect of acetic acid on the cathodic reaction mechanism. It was found that the presence of acetic acid affects only the overall cathodic limiting current, but had no significant effect on the cathodic charge-transfer current. The latter was found to respond only to a change of pH. It was therefore concluded that the buffering effect mechanism is correct.